2016
DOI: 10.12659/msm.898192
|View full text |Cite
|
Sign up to set email alerts
|

Could Heterozygous Beta Thalassemia Provide Protection Against Multiple Sclerosis?

Abstract: BackgroundHeterozygous beta thalassemia (HBT) has been proposed to increase the risk of developing autoimmune disease. Our aim in this study was to examine the prevalence of HBT among multiple sclerosis (MS) patients.Material/MethodsHBT frequency was investigated in our MS group (243 patients with MS). Hemoglobin electrophoresis (HE) was carried out if MS patients had a mean corpuscular volume of (MCV) <80 fL and a mean corpuscular hemoglobin level of (MCH) <27 pg/L according to a complete blood count (CBC). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…( iv ) Two platelet function markers belonging to the group of membrane glycoproteins – selectin P and serum soluble cluster of differentiation 40 ligand (sCD40L) – were present at lower levels in individuals with HBT compared to controls [ 29 ]. Subjects with HBT have a lower frequency of cardiac and cerebral ischemic events than controls in some studies and this difference was supported by a meta-analysis and recently multiple sclerosis is very low in thalassemics [ 30 ].…”
Section: Dear Editormentioning
confidence: 93%
“…( iv ) Two platelet function markers belonging to the group of membrane glycoproteins – selectin P and serum soluble cluster of differentiation 40 ligand (sCD40L) – were present at lower levels in individuals with HBT compared to controls [ 29 ]. Subjects with HBT have a lower frequency of cardiac and cerebral ischemic events than controls in some studies and this difference was supported by a meta-analysis and recently multiple sclerosis is very low in thalassemics [ 30 ].…”
Section: Dear Editormentioning
confidence: 93%
“…Heterozygous β-thalassemia has been suggested to increase the risk of autoimmune diseases ( Galanello and Origa, 2010 ; Altinoz et al, 2012 ). Heterozygous thalassemia protects against multiple sclerosis patients ( Cikrikcioglu et al, 2016 ). It has been observed that β-thalassemia erythrocytes possess lower electrophoretic mobility in physiological media at pH 7.4, owing to the diminished amount of sialic acid on the thalassemic erythrocytes and reduced surface electrical charge ( Mehrishi and Risso, 2016 ; Hristova-Avakumova and Doltchinkova, 2018 ).…”
Section: Introductionmentioning
confidence: 99%